Der Kaiser und Konstantinopel Kommunikation und Konfliktaustrag in einer spätantiken Metropole - Pfeilschifter, Rene (Millennium-Studien / Millennium Studies, 2013)
How did a Late Roman emperor stay on the throne? His position was always precarious, and in contrast to a modern hereditary monarch he could always lose power or even his life to a usurper. The Eastern emperors resided in Constantinople from 395 to 624 without a break. This book shows how they sought the support of the army, the populace, the clergy and the capital`s elite, how they gained it, and how they sometimes lost it. The result is a new picture of the socio-political system of Constantinople and of the Late Roman Empire in general.